Grass–Legume Mixtures Show Potential to Increase Above- and Belowground Biomass Production for Andean Forage-Based Fallows - Meza Retamozo, Katherin Paola (2022)
Descargue el texto completo en el portal de la revista Agronomy: https://doi.org/10.3390/agronomy12010142